2020
DOI: 10.3390/s20216343
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid System of Emotion Evaluation in Physiotherapeutic Procedures

Abstract: Nowadays, the dynamic development of technology allows for the design of systems based on various information sources and their integration into hybrid expert systems. One of the areas of research where such systems are especially helpful is emotion analysis. The sympathetic nervous system controls emotions, while its function is directly reflected by the electrodermal activity (EDA) signal. The presented study aimed to develop a tool and propose a physiological data set to complement the psychological data. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Based on the available literature [ 9 , 10 , 34 , 35 , 81 ], for each part of the EDA, the same statistical parameters as for the heart signals were computed. Furthermore, the following coefficients were also computed from the EDA signal: total energy, mean and median energy of the signal, entropy, coefficient of the slope of the regression line allowing to determine the trend—tonicity of signal, coefficients of regression line shift, a distance of values of consecutive EDA samples from the regression line, number of signal intersections with the regression line and the quadratic metric of the discrepancy between predicted and observed data (obj).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the available literature [ 9 , 10 , 34 , 35 , 81 ], for each part of the EDA, the same statistical parameters as for the heart signals were computed. Furthermore, the following coefficients were also computed from the EDA signal: total energy, mean and median energy of the signal, entropy, coefficient of the slope of the regression line allowing to determine the trend—tonicity of signal, coefficients of regression line shift, a distance of values of consecutive EDA samples from the regression line, number of signal intersections with the regression line and the quadratic metric of the discrepancy between predicted and observed data (obj).…”
Section: Discussionmentioning
confidence: 99%
“…It offers the opportunity to support behavioural diagnostic and analyze the subjects’ physiological reactions in various everyday situations more thoroughly. The approach based on the EDA signal analysis and its features is an example of such attempts [ 10 ]. To objectivize the patient’s emotional state during therapy, a set of analytical parameters—signal errors was proposed, based on which the affect classification accuracy reached the level of 86.37%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies have shown that such meditation is very effective in reducing stress [ 33 ]. Last but not least, Withings Scanwatch [ 196 ] with medical grade ECG and oximeter and two devices from company Empatica: Embrace 2 and E4 should be mentioned [ 197 , 198 , 199 ]. Both are in the form of wristband and can stream the following variables in real time: EDA, wrist temperature and accelerometric signal.…”
Section: Advanced Wearable Stress-metersmentioning
confidence: 99%